The study of sexing of second metacarpal bone from Saurashtra region - Jatin A Chudasama; Mital M Patel; Chintan J Lakhani; Mayank D Javia; Daksha Dixit; T C Singel (Wolters Kluwer Medknow Publications, 2013)
Aim : The aim of the present study is to provide parameters of 2nd metacarpal bones for sex determination from Saurashtra populations. Material and method: Forty two pairs of 2nd metacarpal bones were measured and their dimensions were compared with the dimensions of Spanish and American white population. The mean, SD, t value and p value were calculated, and demarcating point method for sexual dimorphism was employed. Result: Mean interarticular length of 2nd metacarpal was higher in male as compared to female for both sides (right and left) and the difference was statistically highly significant. Mean anteroposterior width at base of 2nd metacarpal was higher in male as compared to female for both sides(right and left),but the difference was statistically insignificant for right side and statistically significant for left side. Conclusion: The present study showed that interarticular length and anteroposterior width at base of 2nd metacarpal are effective parameters for sex determination.